RESEARCH ON INCREASING WORK EFFICIENCY IN THE MECHANISATION OF GERMINATION BED PREPARATION WORKS - Anișoara DUMA COPCEA; Nicoleta MATEOC-SÎRB; Casiana MIHUȚ; Lucian NIȚĂ; Simona NIȚĂ; Teodor MATEOC; Adalbert OKROS; Natalia MOCANU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of this work is weed control by cutting, pulling from the ground and covering with a thin layer of ground, where they can regenerate. The good preparation of the germination bed allows the seed to be covered with a well-aerated, heated soil layer and stand on a more stable and favourably humid soil. The lack of weeds and vegetable residues on the surface of the soil and on the depth of the germination bed gives it the appropriate quality to be sown. The preparation works of the germination bed were carried out at the "December 3, 1990" commercial company from Periam, Timiș County, Romania. The main methods utilized to optimize the use of agricultural aggregates are mathematical programming, direct calculus solutions, and operating nomograms. The purpose of the secondary works performed after ploughing consists in the crushing of soil clogs and of structural soil macro-aggregates in order to carry out the sowing. For the execution of the mechanised scarification works, the preparation of the germination bed and of maize sowing, the types of tractors are chosen according to the technological process of the works and to the biological properties of the crops, depending on the following indicators: light, gauge, size of equipment, plot size, energy consumption of agricultural machines, state of the land, humidity, and manoeuvrability. Soil works have been an integral part of agriculture since the beginnings of farming and they have served several important goals: the preparation of the germination bed, the reduction of soil compaction to increase aeration and allow the root system to develop optimally, the reduction of weeding, the incorporation of fertilizers and amendments, and the management of plant debris. Following the study, we can conclude that the optimization of the use of agricultural aggregates in operation contributes to the reduction of the production expenses, of the specific fuel and material consumption, and of the labour requirement.